Harry Potter and the Order of the Phoenix - Rowling, J. K.; GrandPre, Mary (New York, NY Arthur A. Levine Books, 2003)
When the government of the magic world and authorities at Hogwarts School of Witchcraft and Wizardry refuse to believe in the growing threat of a freshly revived Lord Voldemort, fifteen-year-old Harry Potter finds support from his loyal friends in facing the evil wizard and other new terrors.
"Year 5"--Spine.
Sequel to: Harry Potter and the goblet of fire.
Sequel: Harry Potter and the half-blood prince.
Keywords: Potter, Harry (Fictitious character) -- Juvenile fiction; Granger, Hermione (Fictitious character) -- Juvenile fiction; Weasley, Ron (Fictitious character) -- Juvenile fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Juvenile fiction; Wizards -- Fiction; Magic -- Fiction; Schools -- Fiction; Coming of age -- Fiction